Editorial Notes - Mohd Najib, Sumayyah Aimi (GEOGRAFI, 2025)
On behalf of the Editorial Board, I would like to extend my sincere appreciation to all authors for entrusting  GEOGRAFI with their scholarly work. I am equally grateful to the peer reviewers for their rigorous evaluations, insightful comments, and dedication, which are vital in upholding the academic integrity and quality of the journal. Warm regards and deepest appreciation for your continued support and contribution to GEOGRAFI.